2017
DOI: 10.1080/10715762.2017.1393074
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between oxidative stress and erectile function

Abstract: The aim of this study was to investigate markers of inflammation and oxidative stress in the corpus cavernosum (CC) and to compare levels of inflammatory markers recorded in CC to venous blood from the arm to examine the potential impact of inflammatory parameters on erectile function and endothelial dysfunction in vitro. Ninety-seven patients with no complaint of erectile dysfunction (ED) at inclusion were prospectively included and completed the Erectile Function domain of the IIEF questionnaire. Several par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Tumor necrosis factor-alpha (TNF-α) and interleukin-6 are major pro-inflammatory cytokines produced by hypertrophied adipocytes. They induce inflammatory gene transcript in endothelial cells [39] and suppresses eNOS expression [40]. Corpora cavernosa from TNF-α-infused mice shows attenuated nonadrenergic-noncholinergic nerve-mediated relaxation and suppressed eNOS and nNOS gene expression [41].…”
Section: Obesitymentioning
confidence: 99%
“…Tumor necrosis factor-alpha (TNF-α) and interleukin-6 are major pro-inflammatory cytokines produced by hypertrophied adipocytes. They induce inflammatory gene transcript in endothelial cells [39] and suppresses eNOS expression [40]. Corpora cavernosa from TNF-α-infused mice shows attenuated nonadrenergic-noncholinergic nerve-mediated relaxation and suppressed eNOS and nNOS gene expression [41].…”
Section: Obesitymentioning
confidence: 99%
“…However, the results from two cross-sectional studies examining the relationship between serum markers of oxidative stress and ED are conflicting. In a 2017 cross-sectional study by Thierry et al a negative correlation was found between IL-18 and IL-8 levels and International Index of Erectile Function (IIEF) score, independent of factors such as age, BMI, smoking status, diabetes status, adiponectin, Mox-LDL, and testosterone 11 . Conversely, a 2022 cross-sectional study by Fujita et al did not find a significant correlation between serum markers of oxidative stress and IIEF scores after adjusting for variables such as age, hypertension, diabetes, calcium blocker usage, β-blocker usage, the Brinkman index, and the eGFR 10 .…”
Section: Discussionmentioning
confidence: 97%
“… 29 IL-18 can promote penile tissue damage and dysfunction by affecting the infiltration of downstream monocytes. 30 Studies have shown that IL-18 levels increase in ED patients, thus promoting the activation of downstream inflammatory signaling pathways and ultimately promoting the inflammatory destruction of penile tissue. 19 , 31 Second, IL-18 can further induce the secretion of downstream chemokines through the inflammatory cascade reaction, and promote their chemokines to the site of infection, further exacerbating the inflammatory response.…”
Section: Discussionmentioning
confidence: 99%